2011
DOI: 10.1186/bcr2944
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer biological subtypes and protein expression predict for the preferential distant metastasis sites: a nationwide cohort study

Abstract: IntroductionSome molecular subtypes of breast cancer have preferential sites of distant relapse. The protein expression pattern of the primary tumor may influence the first distant metastasis site.MethodsWe identified from the files of the Finnish Cancer Registry patients diagnosed with breast cancer in five geographical regions Finland in 1991-1992, reviewed the hospital case records, and collected primary tumor tissue. Out of the 2,032 cases identified, 234 developed distant metastases after a median follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
160
3
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 41 publications
26
160
3
5
Order By: Relevance
“…In addition, we observed an organ-specific correlation of DLC1 expression with bone metastasis. Interestingly, we also found in the NKI dataset that DLC1 silencing was associated with bone metastasis only for luminal-type breast tumors (Supplemental Figure 9G), which are known to be predisposed to bone recurrence (42,43), although such findings need to be validated in additional datasets. Previous studies have shown the association of DLC1 silencing with poor prognosis in breast cancer (15).…”
Section: Dlc1 Expression Is Negatively Associated With Pthlh and Bonementioning
confidence: 84%
“…In addition, we observed an organ-specific correlation of DLC1 expression with bone metastasis. Interestingly, we also found in the NKI dataset that DLC1 silencing was associated with bone metastasis only for luminal-type breast tumors (Supplemental Figure 9G), which are known to be predisposed to bone recurrence (42,43), although such findings need to be validated in additional datasets. Previous studies have shown the association of DLC1 silencing with poor prognosis in breast cancer (15).…”
Section: Dlc1 Expression Is Negatively Associated With Pthlh and Bonementioning
confidence: 84%
“…Further, expression levels of the panel of 17 well-justified proteins and their potential associations with the first metastatic site were investigated in the study utilising the data of 2032 BC patients in Finland [31]. Corresponding results revealed the breast tumours that linked to BM do frequently express cytokeratin-5 (P < 0.05), prominin-1 (P < 0.05), nestin (P < 0.1), smooth muscle actin (P < 0.1) being more often ER and PR negative (P < 0.05).…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Several recent studies support the hypothesis that, in invasive breast carcinoma, the gene expression profile of the epithelial component and, therefore, the immunohistochemical profile surrogates of molecular classes, represent biologically distinct diseases with different response to therapy and clinical outcome (12,13). In addition to the epithelial cell autonomous processes, it has been hypothesized that the tumor microenvironment, and particularly CAFs, are able to promote tumor cell proliferation, angiogenesis and metastasis (3,4,14).…”
Section: Discussionmentioning
confidence: 95%